Effect of the terroir and the harvest time on the Kékfrankos grape berries sensorial properties in Eger (Hungary) - Barócsi, Z. (International Journal of Horticultural Science, 2014)
In this research the effects of the production site “terroir” and the harvest time on the most important organoleptic properties of the berries of Kékfrankos (Blaufrankish) grape variety were observed. The follow-up of the maturation process in a given parcel can effectively supplemented by the results of sensorial evaluations of the grape berries. In most cases, the tasters found significant differences in sensorial characteristics of the berries due to the harvest time, although the trends of each parcels were different. Significant differences were frequently found in the result of the observed terroirs.